Right Cerebellar Tuberculosis with Cranial Nerve Palsy in Pulmonary Tuberculosis Patient - I Komang Rusgi Yandi; Isnin Anang Marhana (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Tuberculosis (TB) is a major public health issue. The most devastating clinical manifestations of TB is Central nervous system (CNS) TB. CNS TB is found approximately in 1% of all patients with active TB, and cerebellar TB is rarely reported. CNS TB can present as meningitis, arachnoiditis, tuberculomas, or the uncommon forms of tuberculous subdural empyema and brain abscess.Case: A 23-year-old patient was reported in October 2018 with signs and symptoms of 2-month history of vertigo, headache, vomiting, weakness, fever, blurred vision, lingual palsy, dysmetria, and decrease of consciousness. The patient had a few months of history of cough, contact with a TB patient, his father, and loss of body weight. On admission, the patient had fever (38.50 C) and Glasgow coma score of 13.Discussion: CNS TB can occur in an immunocompromised patient with malnutrition, whether a child or young adult. The patient in this case had risk factors because he is a young adult and had contact with a patient of TB, his father. Based on epidemiology, clinical signs and symptoms, radiological findings, and the result of AFB-stained sputum, the patient was diagnosed with right cerebellar TB and PTB.Conclusion: The high morbidity and mortality characteristics of CNS TB are very important to note, thus the prompt diagnosis and therapy should be done. The specific therapy of ATD combined with surgery seems to provide a good result. The clinical and radiological findings were used as the evaluation of the medication.